FORMATION OF A CLUSTER INNOVATIVE BUSINESS MODEL IN THE CONTEXT OF ENSURING SUSTAINABLE DEVELOPMENT - Nehoda, Serhii F. (Journal of Strategic Economic Research, 2025)
The article proposes the results of a study on the formation of innovatively active enterprises according to the cluster model, justifies the practical use of this integration form to ensure sustainable development. The life cycle of cluster formation is justified, in particular, it is defined by stages: emergence (emergence of a system-forming business idea: basic technology and the presence of prospects for its commercialization), structuring the potential of the future cluster; growth (formation of a number of small business entities connected by sustainable technological chains); maturity (achievement by business entities of a scale of activity sufficient for independent functioning and maximizing the synergistic effect of interaction within the cluster); transformation of the business sector into a segment of an innovative industry cluster. Building a cluster innovative business in the context of sustainable development requires efforts to create favorable conditions for the implementation of scientific, technical and innovative activities. This requires legislative efforts not only at the level of implementing the innovative strategy of the state's socio-economic policy through the adoption and implementation of forecasts and programs of socio-economic development, targeted economic and scientific and technical programs, but also at the level of creating a legal framework for international cooperation in solving the most pressing issues of sustainable development and forming appropriate organizational mechanisms.